Difficult Airway Management of Reconstructive Surgery for Noma (Cancrum oris): A Rare Neglected Disease - Supono, Benny; Adinda Putra Pradhana; I Gusti Putu Sukrana Sidemen; Putu Kurniyanta (HM Publisher, 2024)
Background: Noma is a rare necrotizing gangrenous stomatitis that occurs due to poor oral hygiene and chronic malnutrition. Noma’s survivors usually had significant facial deformities that needed reconstructive surgery as its definitive treatment. However, this facial deformity can result in a difficult airway that is very challenging for anesthesiologists. Case presentation: A 22-year-old male patient had a significant deformity on his left face due to Noma. Preoperative evaluation revealed a potentially difficult airway due to deformity of the maxilla and mandible, malocclusion, inadequate mask seal, and incomplete dentition. Nasal fiberoptic intubation was chosen as the management of a difficult airway in this patient. A tracheostomy was prepared as the emergency invasive airway in the event of failed intubation attempts. Intubation attempts were limited to three times, and the nasal fiberoptic intubation in this patient was successful on the third attempt. The patient was stable, and the airway was safely maintained during the surgery. Conclusion: Detailed and careful perioperative evaluation had vital role assessing potential difficult airway and planning the optimal airway management for patient with facial deformity. Nasal fiberoptic intubation is still the safest choice with high success rate for Noma patient with significant facial deformity.